2006
DOI: 10.1128/ec.5.2.238-247.2006
|View full text |Cite
|
Sign up to set email alerts
|

MNN5 Encodes an Iron-Regulated α-1,2-Mannosyltransferase Important for Protein Glycosylation, Cell Wall Integrity, Morphogenesis, and Virulence in Candida albicans

Abstract: The cell walls of microbial pathogens mediate physical interactions with host cells and hence play a key role in infection. Mannosyltransferases have been shown to determine the cell wall properties and virulence of the pathogenic fungus Candida albicans. We previously identified a C. albicans ␣-1,2-mannosyltransferase, Mnn5, for its novel ability to enhance iron usage in Saccharomyces cerevisiae. Here we have studied the enzymatic properties of purified Mnn5 and characterized its function in its natural host.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…On the other hand, no clear effect on the cell integrity was observed [53]. However, the role of Mnn5 protein (an iron regulated alpyha-1,2 mannosyltransferase) from C.albicans in cell wall integrity maintenance was demonstrated [54]. A mnn5 delta mutant contains a reduced amount of cell wall mannan and hypersensitivity to the cell wall damaging agents.…”
Section: Cell Morphology In Golgi Glycosylation Mutantsmentioning
confidence: 99%
“…On the other hand, no clear effect on the cell integrity was observed [53]. However, the role of Mnn5 protein (an iron regulated alpyha-1,2 mannosyltransferase) from C.albicans in cell wall integrity maintenance was demonstrated [54]. A mnn5 delta mutant contains a reduced amount of cell wall mannan and hypersensitivity to the cell wall damaging agents.…”
Section: Cell Morphology In Golgi Glycosylation Mutantsmentioning
confidence: 99%
“…Mannan, the outermost layer component of the wall, behaves as a potent antigen and has been utilized as the target for the diagnosis of invasive candidiasis. It has been shown that mannosyltransferase deletion mutants of C. albicans have reduced pathogenicity (Bai et al, 2006;Bates et al, 2006;Lengeler et al, 2008). Furthermore, it is known that there are many mannose recognition molecules, such as the mannose receptor, dectin-2, the dendritic-cellspecific intercellular adhesion molecule-3 (ICAM-3)-grabbing non-integrin (DC-SIGN), galectin-3 and mannanbinding protein (Willment & Brown, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that some mannooligosaccharide side chains are correlated with the pathogenicity of the C. albicans cells. 7,24) However, there is no study for the substrate specificity of these enzymes especially for the C. albicans specific mannosyltransferases. To characterize these mannosyltransferases, we need to use the purified recombinant enzyme.…”
Section: Mana1→2mana1→3mana1→3mana1→2mana1→2manmentioning
confidence: 99%
“…[2][3][4] Furthermore, gene deletion experiments demonstrated that the mannan is important for the adherence to host cells and overall virulence. [5][6][7] Mannan consists of a linear a-1,6-linked mannose polymer backbone with side chains composed of a-1,2-, a-1,3-, a-1,6-, and b-1,2-linked mannoses. 8) The side chain mannooligosaccharide sequences are involved in the adhesion or attachment of C. albicans to the macrophage, dendritic cell, or epithelial cell through binding to the mannose-receptor, dectin-2, the dendritic-cell-specific intercellular adhesion molecule-3 (ICAM-3)-grabbing non-integrin (DC-SIGN), and mannan-binding protein.…”
mentioning
confidence: 99%